2006
DOI: 10.1111/j.1365-2249.2006.03123.x
|View full text |Cite
|
Sign up to set email alerts
|

Are increased frequency of macrophage-like and natural killer (NK) cells, together with high levels of NKT and CD4+CD25high T cells balancing activated CD8+ T cells, the key to control Chagas’ disease morbidity?

Abstract: The immunological response during early human Trypanosoma cruzi infection is not completely understood, despite its role in driving the development of distinct clinical manifestations of chronic infection. Herein we report the results of a descriptive flow cytometric immunophenotyping investigation of major and minor peripheral blood leucocyte subpopulations in T. cruzi-infected children, characterizing the early stages of the indeterminate clinical form of Chagas' disease. Our results indicated significant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 44 publications
2
55
0
7
Order By: Relevance
“…The higher expression of IL-10 by cells from indeterminate as compared with cardiac patients was also observed by other groups [43]. Moreover, a high frequency of CD4+CD25 cells has been observed in indeterminate patients [28]. An intriguing finding was that although CD8+ T cells from indeterminate patients display a high frequency of surface CTLA-4 expression, the same cells from cardiac patients have lower surface expression of CTLA-4, while intracellular expression was high [48 •• ].…”
Section: Immunoregulation In the Chronic Phase: Balancing Parasite Comentioning
confidence: 69%
See 1 more Smart Citation
“…The higher expression of IL-10 by cells from indeterminate as compared with cardiac patients was also observed by other groups [43]. Moreover, a high frequency of CD4+CD25 cells has been observed in indeterminate patients [28]. An intriguing finding was that although CD8+ T cells from indeterminate patients display a high frequency of surface CTLA-4 expression, the same cells from cardiac patients have lower surface expression of CTLA-4, while intracellular expression was high [48 •• ].…”
Section: Immunoregulation In the Chronic Phase: Balancing Parasite Comentioning
confidence: 69%
“…Although classic studies have suggested a suppressive response in the early phases of human T. cruzi infection [24,25], it is clear that the immune response mounted is efficient for controlling patent parasitemia. It has been suggested that B-cell activation leading to lytic antibody production is important in parasite elimination during the acute phase [26][27][28]. Although studies of endomyocardial biopsies from acute patients have shown the presence of CD4+ and CD8+ T cells in the inflammatory myocarditis [29], the function of these cells during the acute phase has not been determined.…”
Section: How the Early Encounter Of Trypanosoma Cruzi With Host Cellsmentioning
confidence: 99%
“…Significant differences as shown on days 21 and 28 postinfection for C1 (100 g) vs NaCl (p Ͻ 0.02) and on day 21 postinfection for C1 (10 g) vs NaCl (p Ͻ 0.04). as CD4 ϩ and NK cells in immune protection against infection (12). Based on the protective capacity of miniCD40Ls peptides, one may speculate on the role of these potent immunocompetent cells through CD40-CD40L signaling.…”
Section: The Immunosuppression Induced By T Cruzi Infection Is Impaimentioning
confidence: 99%
“…The role of NK cells has been particularly studied in early and late indeterminate forms of the disease and in CCC patients. In early indeterminate patients, (Girones, et al, 2005, Marin-Neto, et al, 2007 -Avelar, et al, 2006). This profile may be useful to limit parasitemia and confine infection to tissues.…”
Section: Innate Immunitymentioning
confidence: 99%